Impact of forest rehabilitation using Eucalyptus spp. on soil properties at Sg. Betis Forest Reserve, Lojing, Kelantan - Abdul Rahim, Aida Azwani; Abdu, Ariffin; Ali, Norulhuda; Karam Singh, Daljit Singh; S. R., Keeren (Journal of Environmental Science and Pollution Research, 2019)
The forest reserve of Sg. Betis, Lojing, Kelantan is one of the earliest plots to utilize Eucalyptusfor forest rehabilitation purposes, due to the tree’s fast-growing characteristic that is able to accelerate soil restoration for degraded forest.Eucalyptushas a deep root system that can help to hold the soil and is able to reach moisture deep in the ground, in order to survive droughts.This study was conducted to determine the impact of forest rehabilitation on degraded land using Eucalyptusspp.The soil properties were determined prior to planting (October 2017) and after planting (August 2018). Soil analyses showed that there is improvement in selected soil properties after a year of planting.